EFFECTS OF STREET FURNITURE TOWARDS THE LESSENING OF PEDESTRIAN AREA IN BRAGA STREET - Lubis (Jurnal Riset Arsitektur, 2019)
Abstract- Bandung has revitalisation plans stretching throughout the city to promote “smart” and “sustainable” living. One of these projects falls on jl. Braga revitalisation project that has shown significant difference in outlook and in visitor count. The popularity of the street may in return cause discomfort for visitors, as the space allowance per person becomes smaller. This assumption has already been made by Carmona (2003) where he stated that “an unfriendly environment’s pedestrian flow may be increased significantly if the space becomes more pedestrian friendly”. The aim of this study is to evaluate the physical changes made by the revitalisation process in correlation to overcrowding. The discussion will begin by identifying elements withing the street that cause obstructions (obstacles), and a simulation of the circulation space acquired by the obstacle (or the activity it generates) is made in order to calculate the resultant circulation space and measure its overcrowding level. Overall, results show the overcrowding level of the street is constrained and congested. Witihin six out of seven obstructions analysed, it is proved that overcrowding is caused by the acquisition of space of obstacles, whether by itself or by the activities it generates.  Key Words: obstacle, obstruction, overcrowding, jl. Braga